Slow Stroke Back Massage on Postpartum Anxiety: A Quasi-Experimental Study - Astuti, Dwi; Jauhar, Muhamad; Ismail, Wan Ismahanisa (Jurnal Berita Ilmu Keperawatan, 2025)
The postpartum period is very susceptible to anxiety due to the transition process to parenthood and hormonal changes during childbirth and postpartum. Management is carried out by providing Slow Stroke Back Massage. This intervention can make you comfortable and relaxed so that anxiety can be resolved. This article is to determine the effect of Slow Stroke Back Massage on postpartum anxiety. This belongs quasi-experimental research using, one group pretest-postest design. The sampling technique used a total sampling of 76 postpartums. The intervention was carried out for 3 days with a duration of 10 minutes. The research instrument used SOP Slow Stroke Back Massage and the Zung Self-rating Anxiety Scale (ZSAS) anxiety questionnaire. Data analysis was done using Wilcoxon test. The result of this study stated that there is an effect of giving slow stroke back massage on anxiety in postpartum p value (0.000 < 0.05). It can be shortly said that giving Slow Stroke Back Massage can reduce postpartum anxiety.